EVALUATION OF EFL MATERIALS FROM INSTRUCTORS’ AND STUDENTS’ PERSPECTIVES: - Umar, Abdul-Majeed .; M. Eterji, Sami (Gezira Journal of Educational Sciences and Humanities; مجلد 15 عدد 2 (2018), 2019)
For a textbook to realize its ultimate objectives, it should be selected on the bases of  scientific  evaluation criteria  .The current study is conducted to take an analytical look at a new textbook series titled “ Milestones in English ” developed by Oxford University and indorsed to teach English to preparatory college students at Umm-Al-Qura University . The objective of this evaluation is to identify strength and weaknesses (if any) in this book. Two tools were used to collect data for this investigation:  a comprehensive checklist for a sample of (68) instructors and a series of interviews held with a purposively selected sample of (15) students. The data generated through these tools reveal a high level of satisfaction with almost all aspects of Milestones in English. In the main, the findings show that an overwhelming majority of the instructors agree that the layout of Milestone in English is just suitable and its design is perfect. They acknowledge that the book is well organized and its topics   are carefully selected. It is demonstrated that the students are quite satisfied with the activities in this book; however, some of them reserve that there are too many vocabulary items in each lesson and that they need more time to cover the material of this book. The participants have unanimously acknowledged that Milestones   manages to introduce authentic language, and as a multi-skill book, it offers many opportunities for students to practice different skills as individuals, in pairs, and in groups.   It is also revealed that the book adopts some non-traditional assessment techniques; yet some participants call for more challenging tests types. One last important finding in this book is that most participants agree that the content of this book is neither culturally biased nor does it portray negative stereotype. Based on the above findings, the researchers come to the conclusion that Milestones in English with all these advantages is definitely a favourable textbook for the students at UQU and will definitely benefit other similar groups.